Visualizing Fascism The Twentieth-Century Rise of the Global Right - Eley, Geoff; Thomas, Julia Adeney (Duke University Press, 2020)
Visualizing Fascism explores various ways of tracing, displaying, viewing, and interacting with fascism, examining fascism as both a global and aesthetic phenomenon during the twentieth century. It emphasizes transnational and visual qualities in order to refigure ways of establishing visual languages, articulate commentaries on the dynamic nature of national identity, and form both supportive and challenging attitudes about the global right. In particular, this volume seeks to challenge the notion that fascism is primarily a national product of Italy, Japan, and Germany; rather it seeks to locate the rise of fascism and the global right in transnational networks connected by capitalism and imperialism.